Extracellular Adenosine-Mediated Modulation of Regulatory T Cells - Ohta, Akio; Sitkovsky, Michail (Frontiers in Immunology, 2014)
Extracellular adenosine-dependent suppression and redirection of pro-inflammatory activities is mediated by the signaling through adenosine receptors on the surface of most immune cells. The immunosuppression by endogenously-produced adenosine is pathophysiologically significant since inactivation of A2A/A2B adenosine receptor (A2AR/A2BR) and adenosine-producing ecto-enzymes CD39/CD73 results in the higher intensity of immune response and exaggeration of inflammatory damage. Regulatory T cells (Treg) can generate extracellular adenosine, which is implicated in the immunoregulatory activity of Tregs. Interestingly, adenosine has been shown to increase the numbers of Tregs and further promotes their immunoregulatory activity. A2AR-deficiency in Tregs reduces their immunosuppressive efficacy in vivo. Thus, adenosine is not only directly and instantly inhibiting to the immune response through interaction with A2AR/A2BR on the effector cells, but adenosine signaling can recruit other immunoregulatory mechanisms, including Tregs. Such interaction between adenosine and Tregs suggests the presence of a positive feedback mechanism, which further promotes negative regulation of immune system through the establishment of immunosuppressive microenvironment.